2012
DOI: 10.1128/aac.05964-11
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Pharmacodynamics and Antimutant Potentials of Doripenem and Imipenem with Ciprofloxacin-Resistant Pseudomonas aeruginosa in an In Vitro Model

Abstract: To compare the antipseudomonal efficacy of doripenem and imipenem as well as their abilities to restrict the enrichment of resistant Pseudomonas aeruginosa, multiple-dosing regimens of each drug were simulated at comparable values of the cumulative percentages of a 24-h period that the drug concentration exceeds the MIC under steady-state pharmacokinetic conditions (T >MIC ) and ratios of the 24-hour area under the curve (AUC 24 ) to the MIC. Three clinical isolates of ciprofloxacin-resistant P. aeruginosa (MI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
2
6
0
Order By: Relevance
“…Finally, doripenem was comparable to other carbapenems, including imipenem and meropenem, in terms of microbiological eradication rate in the subgroup analysis. All these findings may be well explained by previous in vitro studies [3,4,19,20,21] that showed doripenem had a greater or similar in vitro activity against bacteria, including multi-drug resistant organisms. In this meta-analysis, we did not assess we did not evaluate the association between in vitro activity and the in vivo response of different organisms, especially for antibiotic-resistant pathogens, because the associated information was limited.…”
Section: Discussionsupporting
confidence: 53%
“…Finally, doripenem was comparable to other carbapenems, including imipenem and meropenem, in terms of microbiological eradication rate in the subgroup analysis. All these findings may be well explained by previous in vitro studies [3,4,19,20,21] that showed doripenem had a greater or similar in vitro activity against bacteria, including multi-drug resistant organisms. In this meta-analysis, we did not assess we did not evaluate the association between in vitro activity and the in vivo response of different organisms, especially for antibiotic-resistant pathogens, because the associated information was limited.…”
Section: Discussionsupporting
confidence: 53%
“…The other important criticism of the conventional PKPD indices is that each of the PK components (T, C max and AUC) are dependent covariates (73) and it has been suggested that it is pointless to search for the best predictive index if all are related.…”
Section: Pharmacokinetic-pharmacodynamic Modelsmentioning
confidence: 99%
“…As a final point, PK/PD analysis based on the MIC distributions of the Spanish national survey was applied to estimate the probability of the suppression of the emergence of resistance to the different antimicrobial dosage regimens. Different works have reported the required antimicrobial PK/PD indices to suppress the emergence of P. aeruginosa an-tibiotic resistance [53][54][55][56][57][58][59], although no standardized methods are currently established to determine the antibiotic exposure for the attainment of resistance suppression. In our study, none of the dosage regimens commonly used in ICU patients were able to attain high probabilities of resistance suppression, although ceftazidime/avibactam and ceftolozane/tazobactam 2/1 g q 8 h provide moderate probabilities (>80-90%).…”
Section: Discussionmentioning
confidence: 99%